Rural Health - Bacha, Umar (IntechOpen, 2022)
Rural health is the study of healthcare systems in rural settings. This book presents a comprehensive overview of rural health care and addresses such topics as human resources, maternal mortality in developing countries, safety of healthcare workers, zoonotic and veterinary diseases, and much more. Chapters include case studies and research in the field of rural health.